Enhancing household welfare through perennial crop production in Northern Ghana - Danso-Abbeam, Gideon; Amin, Khama Mohammed; Ogundeji, Abiodun A. (MDPI, 2023)
As Ghana seeks to diversify its agricultural export commodity trade away from its over-reliance on cocoa, empirical evidence is critical to inform policy direction on the implementation of programs to promote such an agenda. The objective of the study was to determine whether farmers who cultivate perennial crops as their primary source of livelihood have better welfare gains than farmers who cultivate perennial crops. The study used cross-sectional data collected from 386 farming households in the northern region of Ghana. The propensity score-matching technique augmented with a control function estimator was employed in order to account for self-selection biases in household characteristics that could invalidate the quality and magnitude of the estimates. Factors identified to positively and significantly influence households’ decision to cultivate perennial crops include number of male adults in a household, farm size, membership of farmer groups, value of agricultural credit, and distance from homestead to the farm. The empirical evidence further indicated that farmers who grow perennial crops have higher welfare gains in terms of consumption expenditure per capita, household income per capita, and farm income per hectare than farmers who grow annual crops as their primary source of income. On the other hand, annual crop farmers have a wider spread of income (income diversification) than perennial crop farmers. Sensitizing farming households to engage in perennial crop production, at the very least, as an alternative source of livelihood, will aid in the fight against poverty and food insecurity, as well as improve Ghana’s macroeconomic balances through agricultural export revenue.
Keywords: Cashew; Control function estimator; Treatment effect; Mango; Propensity score matching